Pengaruh Konflik dan Stres Kerja Terhadap Kinerja Tenaga Kesehatan di RSUD Wangaya Denpasar: The Effect of Conflict and Work Stress on The Performance of Health Workers in Wangaya General Hospital - Wardhana, Zainal Firdaus; Pramesti, Theresia Anita; Maytadewi, Ni Luh Gede Aris; Savitri, Ni Putu Liana Indah (Bali Medika Jurnal, 2021)
Human resources are one of the factors that determine the success of an organization and become the main actor in every activity so that the organization's objectives to be achieved can be needed by the performance of its employees. The factors that affect the performance of health workers, one of which is conflict and work stress. This study aims to determine the effect of conflict and work stress on the performance of health workers in Wangaya General Hospital. This research is a quantitative study with an explanatory research. The measuring instrument in this study was a questionnaire. Conflict and Work Stress has a negative and significant effect on the Performance of Health Workers in Wangaya General Hospital that is equal to 47,5% with t test (4,521 and 5,101) > t table (2,000) with a moderate conflict level of 74,4%; moderate work stress level of 91,9% and moderate performance level of 55,8%. Conflict and Work Stress has a negative and significant effect on the Performance of Health Workers in Wangaya General Hospital.